Does the choice of reference levels of education matter in the ORU earnings equation? - Barry R. Chiswick; Paul W. Miller (Institute for the Study of Labor (IZA), 2009)
This paper examines whether the results of the earnings equation developed in the overeducation/required eduation/under-education (ORU) literature are sensitive to whether the usual or reference levels of education are measured using the Realized Matches or Worker Self-Assessment methods. The analyses are conducted for all male native-born and immigrant workers in the US, by level of skill, and by occupation. While point estimates differ, particularly when earnings equations are estimated for the smaller samples of sub-groups of the workforce, the general findings are robust to this measurement issue. Thus, the answers provided to the typical research questions in the ORU literature on the utilization of schooling are independent of the measure of the usual or reference level of education used in the analyses.
urn:nbn:de:101:1-200910085868
Keywords: I21; J24; J31; J61; F22; 330; Immigrants; skill; schooling; occupations; earnings; rates of return; Einkommensfunktion; Bildungsertrag; Bildungsniveau; Messung; Migranten; Beruf; Qualifikation; Schätzung; USA